Social and Technical Determinants of Perceived Contract Performance: Rules, Autonomy, and Ethics. Issue 3 (2nd July 2016) - Davis, Randall S.; Girth, Amanda M.; Stazyk, Edmund C.
ABSTRACT: Contracting for services represents one mechanism employed to improve the performance of government agencies. While research examining contract performance sheds substantial light on the circumstances under which contracting achieves intended goals, it has rarely considered how the technical and human factors of the contracting process jointly affect contract performance. As a result, relatively little is known about how human factors affect contract performance under shifting technical contingencies. This gap is addressed by exploring how autonomy over contract management and perceived ethical behavior (social factors) are contingent upon changes in contract rules training (a technical factor). The study finds that contract managers who have had more rules training tend to believe that they have less autonomy and view the behaviors of others as unethical. Findings also indicate that more training in contracting rules may inhibit perceived contract performance when mediated by autonomy and perceptions of ethical behaviors.